2003
DOI: 10.1152/ajpgi.00010.2003
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic factor stimulates exocrine pancreatic secretion in the rat through NPR-C receptors

Abstract: Increasing evidence supports the role of atrial natriuretic factor (ANF) in the modulation of gastrointestinal physiology. The effect of ANF on exocrine pancreatic secretion and the possible receptors and pathways involved were studied in vivo. Anesthetized rats were prepared with pancreatic duct cannulation, pyloric ligation, and bile diversion into the duodenum. ANF dose-dependently increased pancreatic secretion of fluid and proteins and enhanced secretin and CCK-evoked response. ANF decreased chloride secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…To examine whether NPR-C mediates pump stimulation, we used two highly selective NPR-C ligands, AP-811 and ANP (4 -23). ANP(4 -23) can elicit a cellular response and is hence regarded as an NPR-C agonist (34). While AP-811 is a highly selective NPR-C ligand (19,38), it is not known whether it is an agonist or an antagonist.…”
Section: Resultsmentioning
confidence: 99%
“…To examine whether NPR-C mediates pump stimulation, we used two highly selective NPR-C ligands, AP-811 and ANP (4 -23). ANP(4 -23) can elicit a cellular response and is hence regarded as an NPR-C agonist (34). While AP-811 is a highly selective NPR-C ligand (19,38), it is not known whether it is an agonist or an antagonist.…”
Section: Resultsmentioning
confidence: 99%
“…María Silvia Ventimiglia, 1 Ana Clara Najenson, 1 Juan Carlos Perazzo, 1 Alejandro Carozzo, 3 Marcelo S Vatta, 2 Carlos A Davio, 3 and Liliana G Bianciotti We previously reported that atrial natriuretic factor (ANF) stimulates secretin-evoked cAMP efflux through multidrug resistanceassociated protein 4 (MRP4) in the exocrine pancreas. Here we sought to establish in vivo whether this mechanism was involved in acute pancreatitis onset in the rat.…”
Section: Blockade Of Multidrug Resistance-associated Proteins Aggravamentioning
confidence: 99%
“…For this purpose, animals were infused with saline (control), secretin (1 U/kg/h) or ANF (1 μg/kg/h) alone or combined for 60 min. The doses of secretin and ANF were obtained from previous doseresponse curves (3). In another group of rats, acute pancreatitis was induced by four repetitive intraperitoneal injections of 40 μg/kg cerulein at hourly intervals and secretin infusion alone, or with ANF for 60 min starting 30 min before the first cerulein injection.…”
Section: Experimental Protocolsmentioning
confidence: 99%
See 2 more Smart Citations